2020
DOI: 10.3390/metabo10050213
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pre-Blood Collection Factors on Plasma Metabolomic Profiles

Abstract: Demographic, lifestyle and biospecimen-related factors at the time of blood collection can influence metabolite levels in epidemiological studies. Identifying the major influences on metabolite concentrations is critical to designing appropriate sample collection protocols and considering covariate adjustment in metabolomics analyses. We examined the association of age, sex, and other short-term pre-blood collection factors (time of day, season, fasting duration, physical activity, NSAID use, smoking and alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Their results showed that fasting status, was not an important source of variability in measurements of most metabolites in their study 39 . Another recent investigation showed that percent differences in metabolite concentrations were negligible across fasting status at the time of blood collection 40 . Nevertheless, in order to minimize the possible confounding by nutritional influence, correlations were adjusted for fasting status 41 .…”
Section: Discussionmentioning
confidence: 98%
“…Their results showed that fasting status, was not an important source of variability in measurements of most metabolites in their study 39 . Another recent investigation showed that percent differences in metabolite concentrations were negligible across fasting status at the time of blood collection 40 . Nevertheless, in order to minimize the possible confounding by nutritional influence, correlations were adjusted for fasting status 41 .…”
Section: Discussionmentioning
confidence: 98%
“…Given known impact of both diet and diurnal variation in hormone levels on serum metabolite concentrations, this may have an impact on the results. Nevertheless, recent data suggest the impact of fasting, activity and time of day have limited impact on plasma metabolite profile [ 32 ]. Moreover we employed a targeted metabolomics approach in the present analysis which limits analysis to only the restricted set of quantified metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…From ColoCare, we identified 110 patients with newly diagnosed colon cancer, recruited at the University Hospital of Heidelberg and the National Center for Tumor Diseases in Heidelberg, Germany 13 . Cancer‐free controls (n = 153) were from the PRÄVENT cohort, with participants recruited in Heidelberg, Germany 14 . All participants were free of colitis ulcerosa, except for two cases and one control.…”
Section: Methodsmentioning
confidence: 99%